Writing papers in psychology : proposals, research papers, literature reviews, poster presentations and concise reports - Rosnow, Ralph L.; Rosnow, Mimi (Belmont, California : Wadsworth Publishing Company, 2012)
Provides frameworks, tips, guidelines, and sample illustrations for college students who are writing research reports or literature reviews that are expected to conform to style recommendations of the American Psychological Association.
1. Getting Started.2. Finding and Retrieving Reference Materials.3. Developing a Proposal.4. Planning the Research Report.5. Organizing the Review Paper.6. Communicating Statistical Information.7. Writing the First Draft.8. Producing the Final Manuscript.9. Preparing Posters and Concise Reports.
Includes index.
Keywords: PSYCHOLOGY -- METHODOLOGY